2017
DOI: 10.3892/mmr.2017.7554
|View full text |Cite
|
Sign up to set email alerts
|

Succinate promotes skeletal muscle protein synthesis via Erk1/2 signaling pathway

Abstract: It is well known that endurance training is effective to attenuate skeletal muscle atrophy. Succinate is a typical TCA metabolite, of which exercise could dramatically increase the content. The present study aimed to investigate the effect of succinate on protein synthesis in skeletal muscle, and try to delineate the underlying mechanism. The in vitro study revealed that succinate dose-dependently increased protein synthesis in C2C12 myotube along with the enhancement of phosphorylation levels of AKT Serine/Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
3
10
0
1
Order By: Relevance
“…We found that succinate-supplemented diet increased serum SUA level ( Fig 1A) but had no effects on the body weight gain ( Fig 1B), food intake ( Fig EV1A), fat mass ( Fig 1C), lean mass ( Fig 1D), gastrocnemius muscle index ( Fig 1E), or liver index ( Fig EV1B). Additionally, consistent with our previous report [23], we found that succinate activated Akt/mTOR cascade and inhibited FoxO3a (Fig EV1C and D). Interestingly, we also found that 1% succinate increased the proportion of small muscle fiber (200-400 lm 2 ), while decreased the proportion of large muscle fiber (600-800 lm 2 ; Fig 1F and G).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We found that succinate-supplemented diet increased serum SUA level ( Fig 1A) but had no effects on the body weight gain ( Fig 1B), food intake ( Fig EV1A), fat mass ( Fig 1C), lean mass ( Fig 1D), gastrocnemius muscle index ( Fig 1E), or liver index ( Fig EV1B). Additionally, consistent with our previous report [23], we found that succinate activated Akt/mTOR cascade and inhibited FoxO3a (Fig EV1C and D). Interestingly, we also found that 1% succinate increased the proportion of small muscle fiber (200-400 lm 2 ), while decreased the proportion of large muscle fiber (600-800 lm 2 ; Fig 1F and G).…”
Section: Resultssupporting
confidence: 93%
“…Consistent with our previous report on the stimulatory effects of succinate on protein synthesis in skeletal muscle [23], we also found dietary supplementation of succinate activated Akt/mTOR cascade and inhibited FoxO3a in WT mice. These regulatory effects of succinate were diminished in SUNCR1 KO mice, suggesting a SUNCR1-mediated activation on protein synthesis.…”
Section: Discussionsupporting
confidence: 93%
“…In the Ts65Dn mouse, the expression pattern of DSCR genes is similar to that in humans (Strippoli et al, 2000) and DSCR protein expression is upregulated in comparison with euploid animals (Baek et al, 2009), thus constituting a possible mechanism to explain our findings. Skeletal muscle hypertrophy is usually characterized by an increase in myofiber protein synthesis (Bodine et al, 2001); accordingly, 1 H NMR showed a tendency in the trisomic mice to an overall increase in metabolites, such as glutamate and succinic acid, which are involved in skeletal muscle protein synthesis (Martins-Bach et al, 2012;Yuan et al, 2017). 1 H NMR also showed a tendency for phosphatidylethanolamine and polyunsaturated fatty acids to increase, and for MUFAs to decrease in muscles of trisomic mice, consistently with the activation of the mTor-pathway-independent mechanism of hypertrophy (Conte et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Since we observed that muscle strength and myofiber size were increased by dietary supplementation of SFe in 20-month-old mice, we investigated whether SFe supplementation increases muscle protein synthesis in TA muscle. Erk1/2 phosphorylation and S6K phosphorylation promote the differentiation and protein synthesis of myotube [23, 24]. We found that the phosphorylated Erk1/2 and S6K protein levels were increased by SFe supplementation in the 20M SFe group than in the 20M CON group (Figure 4).…”
Section: Resultsmentioning
confidence: 89%
“…Muscle protein metabolism is regulated by counterbalanced fluctuations in muscle protein synthesis and muscle protein degradation; however, this balance appears to be disturbed in the elderly and leads to age-induced muscle loss [32, 33]. It is known that Erk1/2 stimulates muscle cell differentiation and protein synthesis [23] and Erk1/2 phosphorylates the S6K1 [24]. Our results showed that both pErk1 and S6K1 were significantly increased in TA muscle of 20M SFe group than in the 20M CON group (Figure 4).…”
Section: Discussionmentioning
confidence: 99%